PHILOSOPHY OF DESCARTES: BASIC INTENTION AND STATUS OF ANTHROPOLOGY ABSTRACT - Anatolii Malivskyi (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
The purpose of the article is to emphasize the insufficiency of reductionist interpretation of Descartes’ heritage and to bring into focus the constitutive role of anthropology in Descartes authentic project. Scientific novelty. Substantiation of anthropology in Descartes’ philosophical structure is based upon recognition of key importance of anthropological intention in previous philosophy as well as anthropological one in philosopher’s own works. Therefore, the insufficiency of established de-anthropologised interpretation of essential intention of Descartes’ doctrine becomes evident. Methodology. The use of phenomenology and hermeneutics enables us to comprehend the key philosopher’s ideas as the manifestation of his personality. The concentration on the interpretation of Descartes ideas as the manifestation of determining influence of external factors is the shortcoming of the established reductionist methodology. Conclusions. It was proved that anthropology that should have been the conclusion of Descartes’ philosophy under conditions of domination of reductionist attitude was withdrawn by the de-anthropologised reality image. The comprehension of the authentic image of Descartes’ philosophy provides special attention to the anthropological element in his ontology.